The Mineral Composition and Hydration Behavior of Cement Clinker Under Different KH Values - Ji, Jiankai; Gou, Mifeng (International Journal of Materials Science and Technology Studies, 2025)
This study investigates the effects of varying lime saturation factors (KH = 0.85, 0.87, 0.90, 0.92) on the mineral composition and hydration behavior of low-heat Portland cement (LHC) clinker, providing theoretical guidance for its industrial production. X-ray diffraction (XRD), scanning electron microscopy (SEM), and hydration heat tests were employed to analyze the phase composition, microstructure, and hydration characteristics of the clinker. The results indicate that as KH increases, the C₃S content rises while the C₂S content decreases, leading to a significant increase in hydration heat peak values and cumulative heat release, as well as enhanced compressive strength. When KH = 0.90, the 7-day hydration heat reaches 276.8 J/g, and the 28-day compressive strength is 43.5 MPa, meeting the GB/T 200-2017 standard for low-heat cement (≤260 J/g) while exhibiting excellent mechanical performance.